Peran Guru dalam Implementasi Hidden Curriculum untuk Pembentukan Kecerdasan Spiritual Siswa di Madrasah Ibtidaiyah - Budi Purwantiningsih; Putri Astrinawati; Nayla Najma Arifin (LP2M STAI Darul Kamal NW Kembang Kerang, 2026)
The rapid advancement of globalization and information technology has significantly influenced the shift in students’ moral values and character formation. Amid these transformations, teachers play a strategic role in nurturing students’ spiritual intelligence through the implementation of the hidden curriculum. This study aims to describe the implementation of the hidden curriculum, the teacher’s role, and the supporting and inhibiting factors in shaping students’ spiritual intelligence at MI Bahrul Ulum Wiyung Surabaya. Employing a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The findings reveal that the hidden curriculum is implemented across dimensions of worship, social behavior, and morality. Teachers serve as role models, mentors, knowledge transmitters, parental figures at school, and evaluators. Supporting factors include discipline in worship and extracurricular religious activities, while inhibiting factors involve limited parental support, differences in students’ religious abilities, and low awareness of spiritual practices.